1999
DOI: 10.1107/s0909049599000898
|View full text |Cite
|
Sign up to set email alerts
|

The optically active center of Er-doped Si produced by laser ablation

Abstract: The local structure of Er-doped Si produced by a laser ablation technique is investigated by Er Lm-edge X-ray absorption fine structure (XAFS). The combination of an extended X-ray absorption fine structure (EXAFS) analysis and a X-ray absorption near edge structure (XANES) simulation indicate the atomic coordination of the optically active center; Er bonded with 6 oxygen atoms distorted form O h symmetry such as a C4v in this Si:Er system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, to the best of our knowledge, a detailed discussion on Ho L 1 -edge XANES spectra is not known. Erbium has much wider application than holmium as a dopant for laser devices, and its L 3 -edge XANES studies have been reported elsewhere. For example, Ishii et al measured the Er L 3 -edge XANES spectra of Er 2 O 3 and Si:Er 2 O 3 thin film prepared by a laser ablation method to investigate the optical activation process of Er and found the second derivatives of the Er L 3 -edge XANES spectra exhibit two minima related to the split 5d orbitals induced by the local configuration of Er . Yb L-edge XANES spectra were also used to investigate the local structure of Yb in various materials. Lanthanide L 1 -edge XANES spectra have been rarely reported, but Quartieri et al used Yb L 1 - and L 3 -edge XANES spectra of synthetic pyrope and grossularite garnets for structural analysis in combination with full multiple scattering calculations .…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, a detailed discussion on Ho L 1 -edge XANES spectra is not known. Erbium has much wider application than holmium as a dopant for laser devices, and its L 3 -edge XANES studies have been reported elsewhere. For example, Ishii et al measured the Er L 3 -edge XANES spectra of Er 2 O 3 and Si:Er 2 O 3 thin film prepared by a laser ablation method to investigate the optical activation process of Er and found the second derivatives of the Er L 3 -edge XANES spectra exhibit two minima related to the split 5d orbitals induced by the local configuration of Er . Yb L-edge XANES spectra were also used to investigate the local structure of Yb in various materials. Lanthanide L 1 -edge XANES spectra have been rarely reported, but Quartieri et al used Yb L 1 - and L 3 -edge XANES spectra of synthetic pyrope and grossularite garnets for structural analysis in combination with full multiple scattering calculations .…”
Section: Introductionmentioning
confidence: 99%
“…10) The UV-vis PL spectra suggest that the local structure modification around Er originates from the movement of active oxygen in ZnO crystal lattice to form optically active Er center. 22) The local structure around Er probably forms a similar pseudooctahedron with C 4v structure 12,23,24) and the most active Er center has been obtained for the sample annealed at 800 C. Both the improved crystallinity of ZnO and the formation of proper oxygen-octahedron around Er lead to the strongest emission at 1535 nm for the thin films annealed at 800 C. When the temperature is up to 1000 C, the preferential orientation of ZnO host is decreasing and Er ion diffusion towards the surface, 25) which relates to the reducing the Er active center as well as the PL intensity in ZnO.…”
Section: Effect Of Annealing Temperaturementioning
confidence: 99%